Synthesis and Crystal Structure of Tetra[μ-O-(dimethylglyoximato-N,N´ )dicopper (II) [Cu2(Hdmg)4] and dinickel(II) and [Ni2(Hdmg)4] - Wan, Jun; Miao, Yan-Fang; Li, Xue-Mei; Zhang, Shu-SHeng (Asian Journal of Chemistry, 2010)
Two new complexes of tetra-[μ-O-(dimethylglyoximato-N,N´)dicopper(lI)] and dinickel(II), Cu2(Hdmg)4 (A) and Ni2(Hdmg)4 (B), (Hdmg- = dimethylglyoxime anion) have been synthesized and their structures determined by X-ray crystallography. Both of the complexes crystallize in the monoclinic system, space group P2(1)/c, with lattice parameters a = 7.1593(1), b = 17.142(1), c = 9.809(2)Å, β = 107.00(1)º, and Z = 4 for A and a = 7.1061(1), b = 17.0437(1), c = 9.7514(2) Å, β = 108.291(l)º and Z = 4 for B. The final R = 0.0351 (0.0487) and wR = 0.0873 (0.1214) based on 1103 (2286) reflections with I > 2σ(1) for A (B). The results indicate that copper(II) and nickel(II) atoms are connected by two μ2 -O-- bridges formed by two hydroxy oxygen atoms in the two oxime groups, respectively; each five-coordinated metal atom possesses a square pyramidal geometry.